Molecular profiles of single circulating tumor cells from early breast cancer patients with different lymph node statuses. Issue 2 (21st November 2022) - Pang, Shuyun; Xu, Shu; Wang, Lulu; Wu, Haiping; Chu, Yanan; Ma, Xueping; Li, Yujiao; Zou, Bingjie; Wang, Shaohua; Zhou, Guohua
Abstract: Background: Characterization of early breast cancer circulating tumor cells (CTCs) may provide valuable information on tumor metastasis. Methods: We used immunomagnetic nanospheres to capture CTCs from the peripheral blood of eight early breast cancer patients and then performed single‐cell RNA sequencing using our proposed bead‐dd‐seq method. Results: CTCs displayed obvious tumor cell characteristics, such as the activation of oxidative stress, proliferation, and promotion of metastasis. CTCs were clustered into two subtypes significantly correlated with the lymph node metastasis status of patients. CTCs in subtype 1 showed a strong metastatic ability because these CTCs have the phenotype of partial epithelial‐mesenchymal transition and enriched transcripts, indicating breast cancer responsiveness and proliferation. Furthermore, DNA damage repair pathways were significantly upregulated in subtype 1. We performed in vitro and in vivo investigations, and found that cellular oxidative stress and further DNA damage existed in CTCs. The activated DNA damage repair pathway in CTCs favors resistance to cisplatin. A checkpoint kinase 1 inhibitor sensitized CTCs to cisplatin in mouse models of breast cancer metastasis. Conclusion: The present study dissects the molecular characteristics of CTCs from early‐stage breast cancer, providing novel insight into the understanding of CTC behavior in breast cancer metastasis. Abstract : Circulating tumor cells (CTCs) were clustered into two subtypes significantly correlated with the lymph node metastasis status of early breast cancer patients. Patients with lymph node metastasis have CTCs that express an epithelial/stem‐like pattern of metastasis initiating cells, while those patients without lymph node metastasis have CTCs that have a mesenchymal signature. The present study dissects the molecular characteristics of CTCs from early‐stage breast cancer, providing novel insight into the understanding of CTC behavior in breast cancer metastasis.